If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6a+5a=-13
We move all terms to the left:
6a+5a-(-13)=0
We add all the numbers together, and all the variables
11a+13=0
We move all terms containing a to the left, all other terms to the right
11a=-13
a=-13/11
a=-1+2/11
| 3/x-1/6x-26=13 | | 10/x-2+3=5x/x-2 | | -5u+3(u-2)=-14 | | (-7x-2x=3)-(9x-5x+4) | | 7(4a-4)=7-7a | | 15-12y=16 | | -22-8x=-5(3x-4) | | 10x-6=58-6x | | 15x-12)=16 | | 15(0)-12y=16 | | -5+4(5x+3)=367 | | (3+5)2x2-13=x | | (5x-12)+(2x+4)+90=180 | | 7x/11-19/14=11/2-5x/8 | | -2/3+3=1/3(-6x+21) | | x^2+5=5/1/16 | | -3r-3r=-18 | | (2x+1/3)+(5x+2/3)=(12x-4) | | 7v/11-19/14=11/2-5v/8 | | 5n+17=-3(1-5n) | | 3x-18=5x5 | | 3=-3p+2p | | x-0.1x=315000 | | 7/9b=49 | | x^2+5=51/16 | | 0.83*x=40 | | (.4)x=3500 | | y-1=5(+2) | | 7=1-4a+2 | | 0.4(x+3)-6(2x-4)=-3.8 | | -4y+7(-5y-2)=8-1(-5-y) | | -8x-7=5x=29 |